Generating Input Ground Motions for Seismic Risk Assessment Using Recorded Ground Motions from the Moderate Magnitude Earthquake - Hae Yeon Ji; Jung Han Kim (Applied Sciences)
To secure the seismic performance of structures, seismic risk assessment is necessary to quantify safety against beyond-design-based earthquakes and seismic design. For the seismic risk assessment of structures, the input ground motions corresponding to the seismic intensity for evaluation are required as seismic loads, which must reflect the tectonic characteristics and site conditions. In this study, ground motions recorded in regions of low to moderate seismicity were used to generate examples of input ground motions for seismic risk assessment. A uniform hazard spectrum (UHS) was used as the target spectrum for risk assessment, following the guidelines. The magnitude and distance parameters of the scenario earthquake for seismic risk assessment were determined via hazard de-aggregation. The empirical Green’s function method (EGFM) was used to match the ground motion recorded at the site with the seismic intensity required for seismic risk assessment. In addition, a spectral matching process was applied to ensure that the input ground motion was compatible with the response spectrum used in seismic risk assessment. In this process, the convergence characteristics of the spectral matching to the target spectrum were analyzed. Consequently, the spectral conditions for selecting the ground motion for the seismic risk assessment were determined.